PENGARUH RASIO KEUANGAN TERHADAP TINGKAT KEBANGKRUTAN PERUSAHAAN MENGGUNAKAN MODEL ALTMAN Z- SCORE (Studi Empiris pada Perusahaan Real Estate dan Properti yang Terdaftar di BEI Tahun 2014 – 2016) - Anla Dina Defitria; Bambang Widarno; Fadjar Harimurti (Universitas Slamet Riyadi, 2020)
The purpose of this study was to determine the effect of financial ratios on bankruptcy rates using the Altman z-score model. This research was conducted on real estate and property companies on the Indonesia Stock Exchange (IDX) in 2014 - 2016. The population consists of 31 companies and a sample of 31 real estate and property companies on the Indonesia Stock Exchange (IDX). The ratio used as an analysis tool is profitability ratio, liquidity, leverage, sales growth (sales growth). The analysis technique used is multiple linear regression analysis. Data was analyzed using SPSS version 21 software. The results showed that the variables of profitability, liquidity, leverage, and sales growth had a positive and significant effect on the level of bankruptcy.